Susceptibility of selected maize seed genotypes to Sitophilus zeamais (Coleoptera: Curculionidae). (March 2019) - Acheampong, A.; Ayertey, J.N.; Eziah, V.Y.; Ifie, B.E.
Abstract: Studies were carried out under laboratory conditions of 25 ± 2 °C and 70 ± 5% RH in an incubator to determine the relative susceptibility of eighteen maize genotypes to attack by the maize weevil, Sitophilus zeamais Motschulsky. The experiment was laid out in a Completely Randomized Design (CRD) with three replications. Adult mortality, number of F1 progeny, weevil development time, susceptibility index, percentage seed damage, percentage weight loss, and weight of powder produced were determined after storage period of three months. The susceptibility index was determined using Dobie's formula and the genotypes were classified into different susceptibility groups. The genotypes exhibited varying degrees of susceptibility to S. zeamais attack. Only Aseda was regarded as resistant and TZE-Y POP STR as moderately resistant to S. zeamais . Kpari-Faako, Tintim, WACCI-M-1215, WACCI-M-1594 and Wang-Dataa were regarded as moderately susceptible to S. zeamais . However, Abontem, Bihilifa, Ewul-Boyu, Sanzal-Sima, TZE-I 17, WACCI-M-1205, WACCI-M-1508 and WACCI-M-1510 were regarded as susceptible genotypes. Furthermore, Aburohemaa, Obaatanpa and Omankwa were regarded as highly susceptible to S. zeamais . Number of F1 progeny, seed damage, seed weight loss, weight of dust produced and seed moisture content had positive relationship with varietal susceptibility while adult weevil mortality, median development period and seed germination after infestation had an inverse relationship with susceptibility in maize. The use of insect resistant genotypes would offer a sustainable way of minimizing postharvest losses of seeds in storage especially for smallholder farmers who keep harvested grains for future use as food and seed.